Russian Teachers’ Perceptions of Kindness and Its Manifestations in Educational Activities - Анна В. Лейбина; Франциско Понс; Юрий И. Семенов (Rossijskij psihologičeskij žurnal., 2020)
Introduction. In recent years, the research on kindness as a character trait has become a subject of increasing interest. The development of kindness in students is inextricably related to the study of kindness in teachers. However, there is the lack of critical attention paid to pedagogical kindness; the phenomenon of kindness has not been studied previously in Russia. This study aims to examine Russian teachers’ perceptions of kindness, its manifestations, and its importance for educational activities. Methods. The study participants (302 teachers) filled out an online questionnaire to define the concept of kindness, the way it manifests itself in educational activities, the importance of pedagogical kindness, and its impact on students, and also provided information on their gender, age, religiosity, presence and number of children, teaching experience, and the age group of students they work with. To process qualitative data, open coding and axial coding were used; multinomial logistic regression was used to identify associations between teachers’ perceptions of kindness and kind actions and sociodemographic variables. Results. The authors (a) identified five thematic categories in the definition of kindness: personal states and qualities, openness to others, understanding of others, external and internal actions and behaviors and (b) proposed a classification for pedagogically kind actions, according to their manifestations during skills and knowledge acquisition, educational activities accompanying educational process, and kindness outside school. No differences were found between teachers’ perceptions of kindness and kind actions and their sociodemographic characteristics. The teachers recognize the importance of pedagogical kindness and its positive impact on students. Discussion. Kindness is not equivalent to helping behavior. However, kindness usually manifests itself in behavior. Therefore, activity theory should be used as a framework for a further study of pedagogical kindness.